Assembly of Retrovirus Capsid-Nucleocapsid Proteins in the Presence of Membranes or RNA - Zuber, Guy (American Society for Microbiology, 2000)
Retrovirus Gag precursor (PrGag) proteins direct the assembly of roughly spherical immature virus particles, while after proteolytic processing events, the Gag capsid (CA) and nucleocapsid (NC) domains condense on viral RNAs to form mature retrovirus core structures. To investigate the process of retroviral morphogenesis, we examined the properties of histidine-tagged (His-tagged) Moloney murine leukemia (M-MuLV) capsid plus nucleocapsid (CANC) (His-MoCANC) proteins in vitro. The His-MoCANC proteins bound RNA, possessed nucleic acid-annealing activities, and assembled into strand, circle (or sphere), and tube forms in the presence of RNA. Image analysis of electron micrographs revealed that tubes were formed by cage-like lattices of CANC proteins surrounding at least two different types of protein-free cage holes. By virtue of a His tag association with nickel-chelating lipids, His-MoCANC proteins also assembled into planar sheets on lipid monolayers, mimicking the membrane-associated immature PrGag protein forms. Membrane-bound His-MoCANC proteins organized into two-dimensional (2D) cage-like lattices that were closely related to the tube forms, and in the presence of both nickel-chelating lipids and RNAs, 2D lattice forms appeared similar to lattices assembled in the absence of RNA. Our observations are consistent with a M-MuLV morphogenesis model in which proteolytic processing of membrane-bound Gag proteins permits CA and NC domains to rearrange from an immature spherical structure to a condensed mature form while maintaining local protein-protein contacts.